Influence of a sport-specific training background on vertical jumping and throwing performance in young female basketball and volleyball players - Battaglia, G.; Paoli, A.; Bellafiore, M.; Bianco, A.; Palma, A. (The Journal of Sports Medicine and Physical Fitness, 2014)
AIM: The purpose of this study was to evaluate the influence of 3 years of sport-specific training background (SSTB) on vertical jumping and throwing performance in young female basketball and volleyball players.